An evaluation of methods of inducing sputum production in patient with suspected lung cancer - Hassan, Maha Shakir (Journal of the Faculty of Medicine Baghdad, 2007)
Background : the major focus of respiratory cytology is the diagnosis of lung cancer , carcinoma of the lung is now reported to be the most commonly diagnosed non- Cutaneous malignancy in the world. Iraq has faced the increase in incidence of this lethal type of cancer. Sputum cytology is a convenient method of screening and diagnosing primary epithelial tumor of the lung which is of many types include fresh smear ,Sacccomanno smear, and mailing container method.Methods : Sputum cytological study was done on 50 patients suspected to have pulmonary carcinoma prepared by fresh smear method ,Saccomanno method ,and mailing containermethod.One, two,or three samples taken from each patient.Slides were prepared and stained by H and E stain and examined thoroughly .The accuracy specificity, and sensitivity was found for each method for comparison.Result and Conclusion : A careful and sometimes frequent sputum samples is very essential in the diagnosis of lung cancer .Preservation and fixation methods are found to facilitate more accurate diagnosis especially in areas far from hospital.